Operating theatre nurses' self‐reported clinical competence in perioperative nursing: A mixed method study - Ann‐Catrin Blomberg; Lillemor Lindwall; Birgitta Bisholt (Wiley, 2019)
Abstract Aims The aim of this study was to investigate how operating theatre nurses (OTNs) self‐rated their clinical competence and describe their experience of important factors for the development of clinical competence in perioperative nursing. Design A cross‐sectional study with a mixed‐method approach was chosen. Data were collected through a modified version of the questionnaire Professional Nurse Self‐Assessment Scale of Clinical Core Competence I, which was supplemented with an open‐ended question. Methods Data were collected from 303 operating theatre nurses in Sweden. Statistics analysis was used to identify the relationship between the participants' background variables. The open‐ended question was analysed by using a qualitative conventional content analysis. Results Academic degree and professional experience of perioperative nursing were significant for the development of clinical competence. Academic degree appeared to affect operating theatre nurses' leadership and cooperation in the surgical team, as well as how consultations took place with other professionals.